3D tumor explant as a novel platform to investigate therapeutic pathways and predictive biomarkers in cancer patients - Rodolfo, Monica; Huber, Veronica; Cossa, Mara; Gallino, Gianfrancesco; Leone, Biagio E.; Vallacchi, Viviana; Rivoltini, Licia; Vergani, Elisabetta (Frontiers in Immunology, 2022)
Immunotherapy with immune checkpoint inhibitors can induce durable clinical responses in different human malignancies but the number of responding patients remains globally modest. The limited therapeutic efficacy of ICI depends on multiple factors, among which the immune suppressive features of the tumor microenvironment play a key role. For this reason, experimental models that enable dissection of the immune-hostile tumor milieu components are required to unravel how to overcome resistance and obtain full-fledged anti-tumor immunity. Recent evidence supports the usefulness of 3D ex vivo systems in retaining features of tumor microenvironment to elucidate molecular and immunologic mechanisms of response and resistance to immune checkpoint blockade. In this perspective article we discuss the recent advances in patient-derived 3D tumor models and their potential in support of treatment decision making in clinical setting. We will also share our experience with dynamic bioreactor tumor explant culture of samples from melanoma and sarcoma patients as a reliable and promising platform to unravel immune responses to immune checkpoint inhibitors.